PEMANFAATAN MEDIA PEMBELAJARAN BERBASIS ICT AUDI VISUAL POWERPOINT UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN PESERTA DIDIK PADA MATA PELAJARAN IPS MATERI INTERAKSI KERUANGAN DALAM KEHIDUPAN DI NEGARA-NEGARA ASEAN DI UPTD SMP NEGERI 8 KUPANG - Boru, Meldy; Rahmawati, Arfita; Hasan, Muhammad Husain (Jurnal Geografi, 2022)
The problem of this research is how to implement ICT audio-visual powerpoint-based learning media and how to use of ICT audio-visual powerpoint-based learning media to improve student learning outcomes. The aim is to find out the implementation of ICT audio-visual powerpoint- based learning media and to find out whether the use of learning media can improve student learning outcomes. This research method includes classroom action research with quantitative descriptive analysis methods, the research subjects is class VIIIH, the sample are 25 students, data collection techniques used tests, observation and documentation. Data analysis is data from observations of the implementation of actions in each cycle. This research conducted in cycles and interrelated. The cyclical actions are planning, implementing, observing, and reflecting. Based on the results of the study, showsed the use of media can improve students' understanding and learning outcomes. Before the action was taken, 21 students, 6 students achieved completeness (28%) and 15 students had not achieved completeness (72%). After the first cycle of action, 16 students (69%) achieved completeness and 7 students (31%) of the 23 students who attended the first cycle test did not complete. After the second cycle of action, 19 participants achieved completeness students (76%) and incomplete 6 students (24%). From the results of this study the researchers stated that this research was successful, namely 76%.